Inhibition of Pkhd1 Impairs Tubulomorphogenesis of Cultured IMCD Cells - Mai, Weiyi (The American Society for Cell Biology, 2005)
Fibrocystin/polyductin (FPC), the gene product of PKHD1, is responsible for autosomal recessive polycystic kidney disease (ARPKD). This disease is characterized by symmetrically large kidneys with ectasia of collecting ducts. In the kidney, FPC predominantly localizes to the apical domain of tubule cells, where it associates with the basal bodies/primary cilia; however, the functional role of this protein is still unknown. In this study, we established stable IMCD (mouse inner medullary collecting duct) cell lines, in which FPC was silenced by short hairpin RNA inhibition (shRNA). We showed that inhibition of FPC disrupted tubulomorphogenesis of IMCD cells grown in three-dimensional cultures. Pkhd1-silenced cells developed abnormalities in cell-cell contact, actin cytoskeleton organization, cell-ECM interactions, cell proliferation, and apoptosis, which may be mediated by dysregulation of extracellular-regulated kinase (ERK) and focal adhesion kinase (FAK) signaling. These alterations in cell function in vitro may explain the characteristics of ARPKD phenotypes in vivo.